Notice of meeting - Morgan, Betty
038-0108-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 4, GREAT SMITH STREET, LONDON, S.W.1. TELEPHONE: ABBEY 2565 February 9th, 1939. A meeting of the Basque Children's Committee will be held on Tuesday, February 14th, 1939, in the House of Commons, Room 15, at 5 p.m. It is very much hoped that you will be able to attend. BETTY MORGAN Organising Secretary. 292/946/38/108(I)